1982
DOI: 10.1113/expphysiol.1982.sp002604
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration Secretion of Amylase From the Parotid Gland of the Rat

Abstract: In anaesthetized rats the parotid saliva secreted during degeneration of the auriculo-temporal nerve contains amylase in fairly constant concentration, the amylase output varying with the secretory rate. The amount of amylase was not reduced by adrenoceptor blocking agents; it was increased by sympathectomy carried out one week in advance. A sympathetic degeneration secretion of amylase could also be demonstrated while the post-ganglionic sympathetic nerves were degenerating; a simultaneous parasympathetic deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In slices of rat parotid glands secretion of amylase can be elicited via muscarinic receptors (Mauers, Herman, Busson, Ovtracht & Rossignol, 1974;Butcher, McBride & Rudich, 1976; Leslie et al 1976). Saliva produced by stimulation of the auriculo-temporal nerve contains amylase (Schneyer & Hall, 1966), and so does the flow caused by degenerative section of this nerve (Asking et al 1982). In the present experiments atropine did not affect the secretion of amylase (Fig.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In slices of rat parotid glands secretion of amylase can be elicited via muscarinic receptors (Mauers, Herman, Busson, Ovtracht & Rossignol, 1974;Butcher, McBride & Rudich, 1976; Leslie et al 1976). Saliva produced by stimulation of the auriculo-temporal nerve contains amylase (Schneyer & Hall, 1966), and so does the flow caused by degenerative section of this nerve (Asking et al 1982). In the present experiments atropine did not affect the secretion of amylase (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…In the present experiments a degenerative output of amylase has been detected in vitro, from lobules of parotid tissue into the surrounding fluid. A preliminary account of some of these experiments has been given (Asking, Emmelin, Gjorstrup & Parsson, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case a vivid secretion of saliva is induced (Delfs & Emmelin 1979) and also after sympathetic denervation a period of secretion, though much less marked can be seen (Delfs & Emmelin 1974). It has furthermore been shown that a significant release of amylase occurs after sympathetic denervation (Asking et al 1981).…”
mentioning
confidence: 99%